(3dWGFa GdeYGQa ajeG dehGSe GdYGe ef GdhXGFas - (3YHO GdQMef Hf CMeO Hf QLH GdMfHdj GdqSdGej GdHZOGOj Ke GdOeTbqj, CHh GdaQL, Rjf GdOjf,J (B795 (3g` s ((3GdLGeY GdeXaQi s)
(3ChdgG (B:s
(3CeG HYO abO bGd Gddg YR hLd hLYdfG Gddjd hGdfgGQ BjJjf aeMhfG BjI Gddjd hLYdfG BjI GdfgGQ eHUQg s
(3BNQgG (B:s
(3gRe GdYRe LfhO Gdghi aCSOi dGJYLhG Ef UdMG cedJ gPg GdfSNI GdeHGQcI HYhf Gddg hMSf JhajbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B118s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs